2000
DOI: 10.1292/jvms.62.1115
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Prostatic Hypertrophy by Osaterone Acetate in Dogs.

Abstract: The prostatic regression effect of oral administration of a new steroidal anti-androgen, osaterone acetate, was investigated in dogs with prostatic hypertrophy. To dogs with prostatic hypertrophy, 0.1-1.0 mg/kg of osaterone acetate was orally administered for one week, and the regression rate was observed. It was shown that administration of osaterone acetate at 0.2 mg/kg or higher, sharply regressed prostatic hypertrophy during the early stage. Therefore, this agent may be clinically applicable as a therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
26
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 15 publications
5
26
0
1
Order By: Relevance
“…Tsumagari et al [14] treated BPH dogs with OSA and showed that the effect persisted for 12 months or longer, emphasizing its superiority over CMA. However, they did not clarify the degree of prostatic regression or duration of persistance [14,15].…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Tsumagari et al [14] treated BPH dogs with OSA and showed that the effect persisted for 12 months or longer, emphasizing its superiority over CMA. However, they did not clarify the degree of prostatic regression or duration of persistance [14,15].…”
mentioning
confidence: 97%
“…Therefore, in this study, we clarified the duration of inhibition of prostatic hypertrophy by OSA using dogs that met the conditions of prostatic hypertrophy proposed by Wheaton et al [15], and investigated the possibility of OSA for clinical application. The prostatic regression by OSA administration was also investigated by comparison with that in orchidectomized dogs.…”
mentioning
confidence: 99%
See 3 more Smart Citations